Careers: workers' perceptions of organizations support for their professional growth - Silva,Júlio Fernando da (2019)
This article deals with the career theme, taking as its context the changes that this concept has undergone over the years: from a traditional approach to a contemporary focus. The research revisits the theme by analyzing organizational policies and practices, as well as (re)cognizing the importance of the worker's own view regarding the phenomenon. Its objective is translated into understanding the management of careers in organizations in the state of Minas Gerais (Brazil), considering the positions adopted by the Human Resources department, and employees' perceptions regarding the possibilities for professional growth and mechanisms for career planning. Secondary data obtained from the "Melhores Empresas para Trabalhar - MEPT - 2016" (The Best Companies to Work For - 2016) survey is taken as a methodological basis. The results point to a concern of the organizations in subsidizing the career development of their professionals, although there are distinctions in this support with respect to the hierarchical levels and size of the company.